SYSTEMATIC LITERATURE REVIEW: HUBUNGAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Sarah Febrianti S; Saiful Bahri; Yuli Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Confidence plays an important role in the academic success of primary school students, with a close link to learning outcomes and influenced by a variety of factors. This study aims to analyze the relationship between confidence and learning outcomes of elementary school students and identify the factors that contribute to its formation. The method used is Systematic Literature Review (SLR) by examining previous research from indexed databases such as Google Scholar, DOAJ, and Garuda. Out of the 200 articles found, the screening process based on abstract and topic relevance resulted in 80 articles. After applying the inclusion and exclusion criteria, there were 15 articles analyzed in depth. The results of the study show that self-confidence has a positive relationship with student learning outcomes, especially in subjects such as mathematics and social sciences. Students with high levels of confidence tend to understand concepts better, have the courage to express their opinions, and are more persistent in facing academic challenges. In addition, factors such as teacher and parent support, a positive learning environment, and interactive learning methods play an important role in increasing student confidence. The implications of this study confirm the importance of learning strategies that can increase student confidence. By understanding the factors that affect student confidence, educators can develop more effective approaches to optimizing student learning outcomes.